Relationship between transforming growth factor beta 1 (TGF-ß1) level and skin tag - Dewi, Sisilia Kesuma; Putra, Imam Budi; Jusuf, Nelva Karmila (Bali medical journal, 2023)
Background: Skin tag, also known as acrochordons, are benign neoplasms that look like a protrusion skin growth. Multifactorial causes of skin tags such as aging, obesity, metabolic and hormonal disorders. One of the mechanisms for the occurrence of skin tags by repeated scratching or friction trauma and continuously triggers an inflammatory response. During inflammation, TGF-ß1 has been activating to prevent the adhesion of neutrophils and T cells to endothelial cells, then limiting the recruitment of inflammatory cells. In addition, TGF-β1 expression is the main promoter in fibroblast proliferation and collagen synthesis as a response to cell repair function. This study aims to determine the relationship between TGF-ß1 level and skin tags. Methods: This observational study has a cross-sectional design of 39 skin tag patients and 40 non-skin tags. Each patient underwent history taking, dermatological examination, then took the blood sampling to analyze the TGF-ß1 level using the ELISA test. These data were statistically analyzed with the Mann-Whitney analytic test. Results: The average TGF-β1 level on skin tags group was 549.05±173.52 ng/ml. Most subjects with skin tags had 1–5 lesions, were 24 people (61.5%). The most common type of skin tag was pedunculated in 9 people (23.1%), followed by the drop form in 6 people (15.3%) and the spherical in 6 people (15.3%). The majority shows that 16 people (41%) have more than one type of skin tag in one region. The results of this study reveal that there is a relationship between TGF-β1 low level and skin tags. Conclusion: There is a significant relationship between TGF-β1 and skin tags.